Communal and efficient movement routines can develop spontaneously through public information use. (21st December 2018) - Riotte-Lambert, Louise; Matthiopoulos, Jason
Abstract: Animal aggregations occur in almost all taxa and can be strongly influential for consumer-resource dynamics and population health. Their adaptive value and underlying mechanisms are thus fundamental questions. Many animals use information about resource locations inadvertently broadcasted by other individuals through visual, acoustic, or olfactory cues. Such simple, involuntary information transfer is commonly employed in groups of social animals. However, it remains unknown whether public information use could have been the initial cause of social aggregations. Here, using agent-based modeling, in the absence of inclusive fitness benefits or direct conspecific attraction, we show that the use of ephemeral public information about resource locations can cause memory-based foragers to spontaneously and permanently aggregate into communal home ranges that take the form of movement circuits (also called traplines) along which individuals travel asynchronously. Even though experienced individuals only rely on their personal memory to inform their movement decisions, we find that the use of public information during the learning phase is very beneficial in the long term because the communal circuits are more efficient than those established by individuals that do not use public information. Our results reveal how simple, inadvertent information transfer between naïve, selfish foragers can cause the emergence of long-term aggregations, which are a prerequisite for the evolution of more complex social behaviors. They also suggest that individuals may not necessarily need to witness the entire sequences of actions performed by others to converge to the same behavioral routines. Abstract : A little bit of mutual spying can lead to the sharing and improvement of movement habits. Using a computer simulation, we find that combined with spatial memory, the use of inadvertently shared information about the location of resource patches, an almost ubiquitous behavioral feature of animals that requires only basic cognitive capacities, leads foragers to spontaneously form permanent communal movement routines that are more efficient than those developed by isolated movers.